Sustentabilidade de assentamentos rurais no estado de Goiás: avaliação comparada entre os assentamentos do nordeste e do sul goiano - Santos, Júnio Gregório Roza dos (2018)
The National Institute of Colonization and Agrarian Reform - INCRA is in charge of putting into practice the policy for agrarian land reform in Brazil, being responsible for the selection of land throughout the country for the creation of rural projects of settlements (PS). This autarchy establishes as a goal, to contribute to sustainable rural development, having as guidelines the democratization of access to land, land regularization and deconcentration of the land properties. Recent studies that discuss the results of the implementation of this settlement policy have considering it to be of low or even null efficacy because it presents problems throughout the implementation of different phases of the settlements that affect the chances of their sustainable development. In view of these deficiencies, the present study selected representative settlements of two regions of the state of Goiás marked by pedomorphological and socioeconomic contrasts - Southern Goiás and Northeast Goiás, in the aim to comparing their indicators to sustainable development. This research was developed in successive steps initiated by the selection of the representative settlements, using the statistical method named Principal Components Analysis (PCA). Then, the elaboration of detailed mapping of land use capacity followed by the methodology presented by Lepsch et al. (2015), Land Use and Cover and Adequacy of Use. Finally, the information produced in the previous phase was used to extract the indicators and to evaluate the sustainability of these selected settlements, considering the Land Use Functions’s methodology developed by Pérez-Soba (2008), by a series of sustainability indicators that are related to several dimensions draw up the sustainability of a system. So, it was selected 16 indicators that cover three group of dimensions, namely: environmental sustainability, economic sustainability and social sustainability. As a result, it was found that regional differences have a strong influence on the chances of sustainable development of PSs. In the Southern the productive conditions of the land are better and there was more attention of the INCRA in the phases of qualification and structuring of the settlement, leading to a greater integration to commercialization circuits and increasing the possibilities of the families in generating income and in securing land. In the Northeast of Goiás, the poor productive conditions of the lands are so intense that they make economic exploration unfeasible. In view of this, they should have been declared unfit for the purposes of agrarian land reform, but they were better able to preserve the fauna and flora. As this did not occur, about 70 families were settled and unfortunately, it was verified that a series of sustainability-dependent indicators of production did not develop, negatively affecting employment and income of the families, contributing to the generation of insecurity, frustration and abandonment of plots. In contrast to Southern where the grate agribusiness, pas by pas, is aggregating them.